Faktor-Faktor Keberhasilan Pembelajaran Bahasa: Perspektif Intake Factors - Nurlaila, Nurlaila (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to identify the factors that determine the success of a learner in language learning. The study used library research methods through procedures, namely data collection, reading and recording data, and data processing. Data collection technique used was documentation with instruments in the form of data cards. Data analysis technique used content analysis. The results showed that the success of learners in language learning was influenced by several factors, namely factors related to students, factors related to teachers, factors related to the learning environment, and factors related to the social environment. Therefore, language teachers must identify the factors that can influence the success of language learning in their class and accommodate all the factors that influence the success of language learning, otherwise the factors that influence failure must be avoided.